Impact of housing allowance programme on the physical and mental health of households in South Korea - Saehim Kim; Saebae Ryu; Kyuhyun Park; Myeong-Hun Lee (PLoS ONE, 2026)
Excessive housing costs significantly affect household financial stability and overall well-being. This study investigated the impact of South Korea’s housing allowance programme on the physical and mental health of household heads, utilising data from the Korea Welfare Panel Study (2009–2021). To overcome selection bias, we employed propensity score matching to construct a comparable control group. We then estimated a two-way fixed effects event study model to assess the dynamic health impacts following the programme’s significant reform in 2015. Our analysis confirms the absence of pre-existing differential trends, supporting the validity of our research design. The results indicate that the policy’s positive effects were not immediate but emerged over time. A statistically significant reduction in depression appeared approximately four years post-reform. For physical health, a consistent and statistically significant improvement was observed from 2017 onwards, highlighting a delayed but sustained positive impact. The findings, validated by a rigorous quasi-experimental design, emphasise the critical role of housing welfare policies in promoting health equity and suggest the benefits of such policies may accumulate over time.